Structural Capacity Gap and Student Overload: A Structural Constraint in The Implementation of Outcome-Based Education in Medical Professional Education - Chrisyanto Tri Pamungkas (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Outcome-Based Education (OBE) emphasizes measurable competency attainment as the primary objective of higher education. In medical professional education, effective OBE implementation requires alignment between policy standards, student enrollment, and clinical training capacity. However, mismatches between these elements may generate structural constraints that affect the effectiveness of policy implementation. This study investigates how the structural imbalance between clerkship student numbers and hospital training capacity constrains the implementation of Outcome-Based Education (OBE). A qualitative case study was conducted at the Faculty of Medicine, Universitas Hang Tuah. Data were collected through in-depth interviews, observation, and institutional documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña (2014). The analytical framework draws on the policy implementation model developed by Van Meter and Van Horn (1975). The findings indicate a significant imbalance between 490 clerkship students and the ideal capacity of the main teaching hospital, RSPAL dr. Ramelan (approximately 300 students). This disparity contributes to an extended average completion duration of 104 weeks (range 94–107 weeks), exceeding the normative standard of approximately 80 weeks. Although implementers demonstrate strong professional commitment, resource limitations emerge as the dominant determinant influencing policy performance. The study concludes that the effectiveness of OBE implementation in medical professional education is structurally dependent on the alignment between student intake and institutional clinical training capacity, rather than solely on the disposition of policy implementers.